Studies on anti-colon cancer potential of nanoformulations of curcumin and succinylated curcumin in mannosylated chitosan - Sourour, Idoudi (2023)
Colon cancer (CRC) is the second leading cause of death and the third most diagnosed cancer worldwide. Although curcumin (CUR) has demonstrated a potent anticancer activity, it is characterized by its poor solubility, low bioavailability, and instability. This study is a projection from a previous investigation where CUR and succinylated CUR (CUR.SA) were separately encapsulated in mannosylated-chitosan nanoparticles (CM-NPs) to form CUR-NPs and CUR.SA-NPs, respectively. Here, we aim to assess the anti-CRC activity of these two nanoformulations. Cytotoxicity studies using CCK-8 assay indicated that both CUR-NPs and CUR.SA-NPs have a dose and time-dependent toxicity towards CRC human cell-lines (HCT116 and SW480), and more cytotoxic compared to free CUR or CUR-SA in a time-dependent manner. A significant induction of early and late apoptosis in the CUR-NPs and CUR.SA-NPs treated CRC cell lines compared to untreated cells was observed. Western blotting analyses confirmed the induction of apoptosis through activation of Caspase signaling compared to untreated cells. Based on the physicochemical properties of CUR-NPs and CUR.SA-NPs along with the data from the in vitro studies, we may conclude these nanoparticle formulations hold very promising attributes, worthy of further investigations for its role in the management of CRC.